Release of lead from Renaissance lead-glazed ceramics from southern Denmark and northern Germany: Implications from acetic acid etching - Rasmussen, Kaare Lund; Milner, George R.; Delbey, Thomas; Jensen, Lisa Kathrine Ivalu; Witte, Frauke; Rehren, Thilo; Kjaer, Ulla; Grinder-Hansen, Poul (Springer, 2020)
Lead-glazed potsherds from archaeological excavations at six Renaissance (1536–1660 CE) sites in southern Denmark and northern Germany have been subjected to etching experiments using 4 wt% acetic acid. The extracts of 45 sherds were analysed by Inductively Coupled Plasma Mass Spectrometry. At one site, the ducal hunting castle of Grøngaard, Pb levels in acid extracts from glazed dishes were so high (up to 29,000 µg Pb cm−2 day−1) that acute toxic effects likely occurred if the dishes were used for serving food containing vinegar. More moderate acid-etching Pb levels were found in dishes from other sites, but they still exceed the WHO critical level if used daily. Acetic acid etching experiments performed on pipkins (three-legged cooking pots with a handle) yielded somewhat lower Pb extract values, averaging ca. 25 µg Pb cm−2 day−1. Taking into account the widespread use of pipkins for cooking, they might easily have led to a higher weekly Pb intake than the use of the moderate-level dishes. The question remains whether such high levels of Pb exposure during meals led to injurious Pb intake. Prior skeletal analyses have shown that medieval to early modern individuals from the area, especially in towns, were exposed to Pb. While exposure could have come from various sources other than lead-glazed ceramics, such as cosmetics, paint, antibacterial ointments, and lead water pipes, widely distributed lead-glazed ceramics had the potential of being a main source of Pb. How the pottery was actually used is uncertain, and it certainly was not evenly distributed across all segments of society, but the etching experiment results suggest that severe poisonous effects could have resulted from the use of lead-glazed Renaissance ceramics.
Keywords: Renaissance; Ceramics; Glazing; Lead; Etching; Northern Europe